Road Accident Mortality Rate of the Iranian Elderly from 2006 to 2008 - Mohammad reza Ghadirzadeh; Reza Fadaye Vatan; Ahmad Ali Akbari kamrani; Keyvan Davatgaran; Seyed Saeed Hashemi Nazari; Seyed Davood Mirtorabi (University of Social Welfare & Rehabilitation Sciences, 2012)
Objectives: Mortality rate in traffic accident is high for Iranian elderly. Twenty percent of elderly people are involved in traffic accident in Iran `s cities every year. Methods & Materials: This study is a descriptive cross sectional study. All data in this field from 2006 to 2008 collected from forensic medicine centers across the country and were analyzed with SPSS software. Results: In general, 12029 deaths due to traffic accident occurred in people over 60 years old in Iran from 2006 to 2008. On average 65% of deaths were occurred in young-old: 34.5% in old group and 0.5% in the old-old group. In these years 19.2% of death in elderly people was occurred in drivers, 56.9% in pedestrians and 23.2% in occupants. On average, each year 46% of deaths in traffic accidents were happened in cities 46.3% on suburban roads, and 6.8% were occurred on rural roads. Conclusion: The rate of traffic accident in Iran is about 20 folds in compare to those of other countries. In years of study mortality rate in old and old-old age groups were increased and in young-old group was decreased. The frequency of deaths in elderly people due to traffic accidents was decreased in suburban roads and increased in urban roads.